HOW DOES ELECTRONIC PAYMENT SYSTEMS AFFECT THE DEVELOPMENT OF E-COMMERCE BUSINESS IN INDONESIA? (JURNAL ECONOMICA : Research of Economic And Economic Education, 2019)
Current technological developments have changed the pattern of public payment transactions. Over the past 5 years electronic payment transactions have risen rapidly to 81%, while the use of checks and demand deposits has dropped by 30%. The ease of transactions with this electronic payment system certainly affects the level of consumption and productivity of the community, especially the trade sector. This study aims to analyze the effect of the electronic payment system on the development of e-commerce business in Indonesia. This study uses a random-effect panel data regression analysis method using quarterly data obtained from Bank Indonesia, the Badan Pusat Statistik, and various survey institutions related to e-commerce activities. The results of this study indicate that the long-term outcome, simultaneously variable electronic payment and real GDP has a positive and significant influence on the development of online business (e-commerce) in Indonesia. Conversely, in the short term, no significant relationship was found between the three variables.